Strategi Operasional Baitul Maal Wa Tanwil dalam Menghadapi Ketidakpastian Lingkungan - Falah, Muhammad Helmi; Husnan, Lalu Hamdani; Sokarina, Ayudia (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
Previous studies related to the Baitul Maal Wa Tanwil (BMT) problem generally only made an inventory of the problems without connecting these various problems and their implications for BMT's strategy in developing its organization. Therefore, researchers used exploratory qualitative research methods to answer research questions using semi-structured interview methods, triangulation of sources and theory. This study aims to explore the operational strategy of BMT in carrying out its dual function. The results of the study reveal that the operational strategy of BMT is to focus on the role of baitul tamwil (business institution) by tending to override the role of baitul maal (social institution). This pragmatism is caused by various challenges such as limited funds, the many philanthropic institutions, overlapping regulations on zakat management by BMTs, and managerial competence. These challenges not only make BMT focus on its business institutions, but also make BMT focus on limited circles so that financial inclusion has not been achieved. Keywords: BMT; Pragmatism; Islamic Economics